2007
DOI: 10.1086/521627
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Mannan‐Binding Lectin Gene Polymorphism and Clinical Leprosy: New Insight into an Old Paradigm

Abstract: These results suggest that MBL2-gene polymorphisms play a role in susceptibility to leprosy per se and in the clinical progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 40 publications
9
83
3
2
Order By: Relevance
“…Consistent with previous reports that higher MBL expression is a risk factor for mycobacterial disease, the "high"-expressing haplotype LYPA was also more frequent in patients than in controls (OR, 2.25; P ϭ 0.02, adjusted analysis). There was also a nonsignificant association of this haplotype with lepromatous and borderline leprosy (71). In a second study, Fitness et al analyzed a single exon 1 polymorphism but found no association in Malawi (93).…”
Section: Innate Immune Effector Molecules and Serum Proteinsmentioning
confidence: 98%
See 3 more Smart Citations
“…Consistent with previous reports that higher MBL expression is a risk factor for mycobacterial disease, the "high"-expressing haplotype LYPA was also more frequent in patients than in controls (OR, 2.25; P ϭ 0.02, adjusted analysis). There was also a nonsignificant association of this haplotype with lepromatous and borderline leprosy (71). In a second study, Fitness et al analyzed a single exon 1 polymorphism but found no association in Malawi (93).…”
Section: Innate Immune Effector Molecules and Serum Proteinsmentioning
confidence: 98%
“…MBL deficiency was previously correlated with homozygosity or compound heterozygosity for six well-described SNPs of the MBL2 gene: two promoter SNPs (at positions Ϫ550 [H/L] and Ϫ221 [Y/X]), a 5Ј untranslated region SNP (position ϩ4 [P/Q]), and three nonsynonymous SNPs in exon 1 (allele D, R52C; allele B, G54D; and allele C, G57E) (106). These loci are in strong linkage disequilibrium, resulting in only seven common haplotypes from combinations of these six alleles (71,76,106,136).…”
Section: Innate Immune Effector Molecules and Serum Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the same polymorphisms mediate a certain level of protection against mycobacterial infections with M. tuberculosis and M. leprae [17,18]. Th e reason being that the bacteria, which are covered with MBL are more easily taken up by macrophages which is their preferred host cell.…”
Section: The Serum Proteins Mannose-binding Lectin and Fi Colin-2 In mentioning
confidence: 99%